Mechanisms of angiogenesis in tumour - Zhang, Run; Yao, Yutong; Gao, Hanwei; Hu, Xin (Frontiers in Oncology, 2024)
Angiogenesis is essential for tumour growth and metastasis. Antiangiogenic factor-targeting drugs have been approved as first line agents in a variety of oncology treatments. Clinical drugs frequently target the VEGF signalling pathway during sprouting angiogenesis. Accumulating evidence suggests that tumours can evade antiangiogenic therapy through other angiogenesis mechanisms in addition to the vascular sprouting mechanism involving endothelial cells. These mechanisms include (1) sprouting angiogenesis, (2) vasculogenic mimicry, (3) vessel intussusception, (4) vascular co-option, (5) cancer stem cell-derived angiogenesis, and (6) bone marrow-derived angiogenesis. Other non-sprouting angiogenic mechanisms are not entirely dependent on the VEGF signalling pathway. In clinical practice, the conversion of vascular mechanisms is closely related to the enhancement of tumour drug resistance, which often leads to clinical treatment failure. This article summarizes recent studies on six processes of tumour angiogenesis and provides suggestions for developing more effective techniques to improve the efficacy of antiangiogenic treatment.